Odyssey Self Reflection - Belaga Ayam / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
My idea was about the movement of belaga ayam, of which uniqueness had inspired me to create artworks consisting of drawing, printmaking and sculpture. My point of view in my artworks centred on the scene of roosters fighting. The elements and principles in the artwork concerned the movement, the highlighted form of rooster during the fight, texture, line and value, systematics of the rooster chicken. I made use of existing materials for my sculpture such as aluminium, plastic bottle, polystyrene, iron, cement and wire. I employed the intaglio technique for the printmaking artwork, meanwhile, for drawing, I chose charcoal pencil for material and plywood for media.